Aquisição incidental de vocabulário em língua inglesa através da leitura: uma abordagem steam para o ensino de inglês e programação - Lopes, Leonardo Gomes (2025)
This study explores the challenges of teaching/learning English as a foreign language in Brazilian public schools, focusing on the inadequacy of traditional pedagogical methodologies. It proposes adopting the STEAM (English acronym for science, technology, engineering, arts and mathematics) educational approach to teach English in tandem with basic programming concepts. It aims to examine the incidental acquisition of English vocabulary through reading in a public school in Fortaleza, Ceará. Theoretical contributions from Ellis (1994, 1997, 1999), Krashen (1981), Nation (1990, 2001), Coady (1997), Laufer (1997), Paribakht and Wesche (1997, 1999), among others, provide a comprehensive foundation for understanding vocabulary acquisition in English, enriching the understanding of the phenomenon. Central to this investigation is the Task-Induced Involvement Load Hypothesis, developed by Laufer and Hulstijn (2001), which posits that the depth of vocabulary acquisition is influenced by three components: need (the motivation to learn a word), search (the effort to find the meaning of a word), and evaluation (the comparison of a word’s meaning within a specific context). The hypothesis suggests that tasks generating higher involvement load (IL) result in more effective vocabulary learning. The specific objectives were: to assess participants’ prior vocabulary knowledge, to measure the acquisition of target words following the intervention, and to analyze the effect of task order – in reading activities with different levels of IL – on vocabulary learning outcomes. For this, Group A was initially exposed to activities with low IL, followed by activities with high IL, while Group B followed the reverse order. The methodological design was divided into three stages. Initially, a pre-test with 25 items (20 target words and 5 distractors) was applied to evaluate the participants' initial vocabulary knowledge. Then, a specific didactic intervention was conducted, in which students in the 6th grade of elementary school participated in a programming workshop lasting 600 class hours, using a material written in English designed based on Apple Inc.'s Swift Playgrounds application. The pre-test results indicated a limited initial knowledge of the target words (8% of the participants in Group A demonstrated receptive knowledge of the target words and 3% in Group B). The post-test showed vocabulary gains in both groups, confirming the hypothesis that reading can promote incidental vocabulary acquisition. However, the analysis based on the two-proportion comparison test did not reveal statistically significant differences between the experimental conditions regarding the proportion of correctly recognized words (² = 2.095, p = 0.148; CI 95%: -0.023 a 0.155). These results indicate that the order of exposure to the tasks did not result in significant performance differences. These findings suggest that the observed variation may have occurred at random and reinforce the need for additional investigations that consider other intervening variables.